Social-Economic and Cultural Aspects of the Thar Region of Rajasthan - Panwar, Suman (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Thar Desert, also known as the Great Indian Desert, occupies nearly two-thirds of western Rajasthan and stands as one of India’s most distinctive ecological, geographical, and cultural regions. Spanning the districts of Jaisalmer, Barmer, Bikaner, Jodhpur, and Jalore, the Thar is characterized by its extreme climatic conditions, scarce rainfall, sandy terrain, and fragile ecosystem. Yet, in this seemingly inhospitable environment, human civilization has not only sustained itself for centuries but has flourished through exceptional adaptability, community cohesion and cultural creativity. Economically, the region has transitioned from traditional subsistence activities to modern sectors such as tourism, renewable energy, and handicrafts, reflecting a gradual yet significant transformation in livelihood patterns. Culturally, the Thar embodies Rajasthan’s artistic soul—its folk music, dance, crafts, attire and oral traditions serve as living archives of identity and heritage. Ultimately, this research reveals that the Thar Desert is not merely a barren landscape but a dynamic human and cultural ecosystem, where resilience and tradition harmonize with change and innovation.